2020
DOI: 10.33024/jikk.v7i1.2348
|View full text |Cite
|
Sign up to set email alerts
|

Studi Literatur: Faktor-Faktor Yang Mempengaruhi Kualitas Hidup Pasien Penderita Gagal Jantung Di Indonesia

Abstract: Penilaian kualitas hidup pada pasien gagal jantung merupakan salah satu tolak ukur keberhasilan terapi. Studi literatur ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kualitas hidup pada pasien gagal jantung di Indonesia. Metode studi literatur dilakukan melalui penelusuran artikel publikasi pada MEDLINE, Google scholar, PubMed serta Proquest dengan kata kunci gagal jantung, kualitas hidup, heart failure, quality of life, dan HRQoL. Penelusuran literatur dari terbitan tahun 2015-2019 deng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
(4 reference statements)
0
3
0
2
Order By: Relevance
“…Table 1 presents a univariate analysis to determine the characteristics of respondents and table 2 presents a bivariate analysis to analyze the relationship between the two variables using the Spearman Rank non-parametric correlation test. [11].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents a univariate analysis to determine the characteristics of respondents and table 2 presents a bivariate analysis to analyze the relationship between the two variables using the Spearman Rank non-parametric correlation test. [11].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, another study found that heart failure patients with depression had a 1.36 times greater risk of death than those with diastolic. however, in heart failure patients with normal or decreased ejection fraction, the same limitation of physical activity is still found, according to the patient's NYHA degree (Izzuddin et al, 2020).…”
Section: Factors That Affect the Quality Of Life Of Patients With Cor...mentioning
confidence: 85%
“…this is contrary to research (Apers et al, 2016) which states that the most jobs in people with heart disease are civil servants/ private. Patients who have higher education will find it easier to get information regarding the conditions that are being experienced, as well as preventing those that will arise, as well as how to treat themselves with these conditions (Pudiarifanti et al, 2015).…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…Selain itu, ibu rumah tangga rentan terhadap risiko CHF karena sering memikirkan masalah rumah tangga dengan perasaan, hal tersebut menyebabkan ibu rumah tangga sering kali merasa khawatir dan merasa cemas setiap memiliki masalah [12]. Kondisi sesak yang dirasakan oleh pasien memengaruhi aktivitas sehari-hari, sesak pada penderita CHF menyebabkan kelelahan yang mengganggu aktivitas penderita pada tingkatan sedang seperti memasak, mandi, mencuci atau berpakaian [3].…”
Section: Hasil Dan Pembahasanunclassified